2014
DOI: 10.1136/jnnp-2014-308992
|View full text |Cite
|
Sign up to set email alerts
|

The network topology of aneurysmal subarachnoid haemorrhage

Abstract: URL: http://www.clinicaltrials.gov; Identifier: NCT00111085.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Such standards of monitoring brain pathology may complement alternate representations of complex data sets 88 with the ultimate ambitious goal of a wholesystem approach to neurocritical care. Such an approach removes some obstacles by replacing a ''black box'' that only shows outputs devoid of context, with information about the evolution of disease process, the homeostatic responses, and therapeutic interventions, along with means to tease apart the effects of these interactions.…”
Section: Neurocritical Care As a Systems Processmentioning
confidence: 99%
“…Such standards of monitoring brain pathology may complement alternate representations of complex data sets 88 with the ultimate ambitious goal of a wholesystem approach to neurocritical care. Such an approach removes some obstacles by replacing a ''black box'' that only shows outputs devoid of context, with information about the evolution of disease process, the homeostatic responses, and therapeutic interventions, along with means to tease apart the effects of these interactions.…”
Section: Neurocritical Care As a Systems Processmentioning
confidence: 99%
“…[2][3][4] In acute ischemic stroke, hypoalbuminemia is associated with poor outcome, [5][6][7][8] and is a strong predictor of early death in subarachnoid hemorrhage. [9,10] Little is known about the significance of serum albumin levels as a prognostic factor in spontaneous intracerebral hemorrhage (ICH). [11] ICH induces an acute-phase inflammatory response (APR).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…These physiological variables consistently accompanied poor performance in previously published studies [60][61][62][63]. Earlier studies reported that low albumin levels are associated with increased morbidity and mortality in aSAH patients [64][65][66]. Hypoalbuminemia can occur due to reduced synthesis, increased loss, or altered distribution in extracellular and intracellular spaces.…”
Section: Discussionmentioning
confidence: 66%